Digitizing the School Administration Management System at SMAN 12 Bandung and its Evaluation with the System Usability Scale - M Luthfi Zulfikar; Rosihan Ari Yuana; Nurcahya Pradana Taufik Prakisya (Pendidikan Teknik Informatika dan Komputer, Universitas Sebelas Maret, 2022)
Education administration is one of the vital information in learning activities. Education administration can increase the productivity of teachers and will make learning activities more focused and structured. Digitalization of education administration will help teachers manage education administration, especially planning for learning. Moreover, this application will help teachers assign students scores based on their attitudes. This system will use Laravel as a base along with a spiral model for the SDLC, and use the System of Usability Scale For Evaluation (SUS). This application is Considered easy to use because it gets the 'acceptance' grade based on acceptance, a